Measuring Globalization Better Trade Statistics for Better Policy - Houseman, Susan N. (W.E. Upjohn Institute, 2015)
Understanding the impacts of globalization requires good data, and national statistical systems were not designed to measure many of the transactions occurring in today's global economy. The chapters in this two-volume set identify biases and gaps in national statistics, examine the magnitude of the problems they pose, and propose solutions to address significant biases and fill key data gaps.